Influence of heat treatment on the properties of MgO thin films as dielectric layer / Habibah Z. ... [et al.] - Z., Habibah; L.N., Ismail; R.A., Bakar; M., Rusop (2012)
Physical properties such as high melting point, low heat capacity and high bonding strength of magnesium oxide, MgO could be get give an advantage to MgO to be used as the dielectric layer. Besides that, MgO also has large band gap (7.8 eV) and high dielectric constant (9.8) could be potentially used as a buffer layer for ferroelectric material. In this work, MgO with 0.2M concentration were prepared using sol-gel technique. Magnesium acetate tetrahydrate, ethanol and nitric acid used as precursor, solvent and stabilizer respectively. The MgO solutions were then deposited on the cleaned glass by using spin-coating technique. The thin film deposition is repeated for 8 times for uniformity purpose. The electrical and dielectric properties of MgO are identified by observing its resistivity, dielectric constant, dielectric loss and its surface morphology in terms of annealing temperature. Since high deposition temperature is needed in order to obtain high quality of MgO films and also due to the limitation of glass, the annealing temperature is varied from 400°C to 500°C with 25°C interval. The experimental results show that annealing temperature is inversely proportional to the thickness of MgO films due to the merging activity of the particle. MgO film annealed at 500ºC has been chosen as a good dielectric layer since it has a good electrical, dielectric and structural properties.